To solve for t in the equation h(t) = 16t^2 + 60t + 30, we can set h(t) equal to a specific value and solve for t.
Let's solve for h(t) = 0:
0 = 16t^2 + 60t + 30
To simplify the equation, we can divide all terms by 2:
0 = 8t^2 + 30t + 15
Now, let's solve this quadratic equation. We can either factor it or use the quadratic formula.
Since the equation doesn't factor easily, let's use the quadratic formula:
t = (-b ± √(b^2 - 4ac)) / (2a)
For our equation, a = 8, b = 30, and c = 15.
t = (-30 ± √(30^2 - 4(8)(15))) / (2(8))
Simplifying further:
t = (-30 ± √(900 - 480)) / 16
t = (-30 ± √420) / 16
Now, we have two possible solutions for t:
t = (-30 + √420) / 16
and
t = (-30 - √420) / 16
These are the solutions for t in the equation h(t) = 16t^2 + 60t + 30.
solve for t. h(t)=16t^2+60t+30
1 answer